Penyusunan Dokumen Standar Operasional Prosedur (SOP) Wisata Edukasi Kampung Nanas Palaan - Resmiatini, Erna; Sari, Niki Puspita (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2022)
This research is a qualitative research that aims to solve the problems faced by management of Kampung Nanas Educational Tourism. The problem is the absence of SOP documents for various activities. Specifically, the objectives to be achieved through this research are identifying and compiling SOP documents for Kampung Nanas Educational Tourism. The research method is a qualitative research method with data collection techniques through interviews and documentation. The data analysis technique is the Miles and Huberman model. The results obtained through this research are the SOP for Educational Tourism in Kampung Nanas which is divided into four areas, namely: (1) SOP for Secretariat, Personnel and General Affairs, (2) SOP for Tourism Management, (3) SOP for Finance, (4) SOP for Tourism Promotion. These results are expected to provide great benefits for the management of Kampung Nanas Educational Tourism in carrying out their duties.